Literasi Kesehatan dan Perilaku Perawatan Kaki Melalui Terapi 3F (Foot Assessment, Foot Care, Follow Up) - Muhammad Ikhwan Siswanto; Hidayah; Mahin Ridlo Ronas; Kharisma Pratama (Literasi Intelektual, 2026)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Proper foot care is essential for patients with diabetes mellitus to prevent diabetic foot ulcers. Foot care behavior can be influenced by several factors, one of which is health literacy. Low adherence of patients with DM to foot care practices is partly due to low levels of health literacy. Objective: This study aimed to determine the relationship between health literacy and foot care behavior among patients with type 2 diabetes mellitus through the 3F therapy (foot assessment, foot care, and follow-up) at Kitamura Clinic, Pontianak. Methods: This study employed a quantitative approach with a cross-sectional design. Samples were obtained using consecutive sampling, involving 35 respondents. The research instruments were questionnaires used to measure health literacy levels and foot care behavior. Data analysis was conducted using the Spearman’s rank correlation test. Results: The Spearman’s rank correlation test showed a p value of 0.049 (< 0.05), indicating a significant relationship between health literacy and foot care behavior through the 3F therapy. The correlation coefficient was 0.335, indicating a positive relationship with weak correlation strength. Conclusion: There is a significant relationship between health literacy and foot care behavior through the 3F therapy (Foot Assessment, Foot Care, Follow-Up), with a positive direction and weak correlation strength, indicating that higher health literacy is associated with better foot care practices among patients with type 2 diabetes mellitus.